PERAN PEMERINTAH DAERAH DALAM PROSES PENYELESAIAN KONFLIK LAHAN DI DAERAH PERBATASAN (Studi Kasus Desa Pulau Jambu Kecamatan Cerenti Kabupaten Kuantan Singingi Dengan Desa Selunak Kecamatan Batang Peranap Kabupaten Indragiri Hulu Tahun 2011-2013) - Delzi Syofiana Dewi; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The research present describe the land conflict between are Pulau Jambu Village Cerenti District Kuantan Singingi Regency and Selunak Village Batang Peranap District Indragiri Hulu Regency. This conflict reason is PT. Asia Sawit Makmur Jaya (ASMJ) come to Pulau Jambu Village Cerenti District Kuantan Singingi Regency for opened a plantation land and get permit from the regent of Kuantan Singingi Regency. But, society of Selunak Village Batang Peranap District Indragiri Hulu Regency felt are founding they land is inside to the location permit, so that society of Selunak Village to claim for return them’s land because that are half of society Selunak Village occupation location. But the company is can’t answered that the request from society of Selunak Village, with the reason that land to represent of the land Pulau Jambu Village Cerenti District Kuantan Singingi Regency adjust with the permit who are given of Regent of Kuantan Singingi Regency. This conflict be continue until to aroused a fight between society Selunak Village, Pulau Jambu Village and the company.The research use the method are qualitative methods that analyze problem research by describe the subject and objects condition based on real fact. This research use location in Pulau Jambu Village Cerenti District Kuantan Singingi Regency and Selunak Village Batang Peranap District Indragiri Hulu Regency and researcher collect data from books, government regulation, journal, mass media, website and deep interview with some informan. The research use the theory of conflict and district government. Purpose of this research is for finding causes factor land conflict between Pulau Jambu Village and Selunak Village, and to knowing what the expedient that doing of district government in finished this land conflict.The conclution of this research are the conflict until now still in finishing process, each of them fixed that the land are owned. Until each of them still find out solution to finding good finishing for them.Keywords : Conflict, District Government,relic land.